Why and How to Internationalise Law Curriculum Content - Tihomir Mijatov (Legal Education Review)
Legal academics’ drive over the last 40 years to expand their research horizons has exposed their research to the possibility of extra-disciplinary assessment and critique. This is particularly true of the assessment of legal PhDs, where examiners from non-legal disciplines are increasingly being used. But disciplinary outsiders are assessing the quality of legal research in other settings as well, such as the competitive grants applications process and the peer review of articles submitted to interdisciplinary journals. This article argues that legal academics need to respond to this challenge, but that the way they respond depends on the distinction between traditional doctrinal research and the other kinds of legal research that have emerged over the last 40 years. The challenge in the former case is to defend doctrinal research against the charge that, as a form of applied social science research, its practitioners should conform to the research standards applicable in that set of disciplines. A proper understanding of the purpose and methods of doctrinal research suggests that this charge is not well made out, and that there is a strong case for arguing that the quality of doctrinal research should be assessed by researchers familiar with the particular area of law concerned. In the case of the other forms of legal research that have emerged over the last forty years, on the other hand, legal academics do need to respond to the demand for greater methodological rigour. This is especially true of the particular kind of socio-legal research in which many legal academics engage, which mixes the internal perspective of the trained legal professional with the external perspective of the social sciences. But it is also true of the other main categories of legal research, including legal philosophy, comparative legal research and critical approaches. In all these cases, legal researchers need to conform to the standards of the disciplines on which they are drawing.